The acceptance of satay innovation for domestic tourism. - Hamidi, Nurul Hassanah; Saad, Mazni (2020)
Innovations are a process of recreating or bring a new product on the market for the purpose of increasing sales and performance efficiency. It has influenced and altered almost every aspect life from food, lifestyle, traditions, and daily lifestyle. The innovation of Satay experienced a huge alteration as time pass by it has been forgotten as a Malaysian food heritage. It is happening due to poor marketing and promotion which inclusion of foreign food culture that has undermined the tradition of traditional food. Therefore, this research aims to identify the characteristics of innovation on satay and investigate local acceptance towards innovation towards satay. The study was carried out by implementing a qualitative research approach by conducting a face-to-face interview with selected satay operator. The study involved thematical analysis in line with phenomenological approach. Hence, the research outcome may offer understanding to strengthen of promotion and marketing in Malaysian food heritage.